Home care in COVID-19 patients with the home-quarantined condition: A study from Iran - Afshari, Poorandokht; Beheshti-Nasab, Maryam; Maraghi, Elham; Sadeghi, Simin; Sanjari, Nafiseh; Zarea, Kourosh (Frontiers in Public Health, 2022)
Objectives: During the COVID-19 home quarantines, home care services may act as an auxiliary component of health care services, which reduces the burden on the health care system. This study aimed to investigate the type of care and the people providing home care for patients with Covid-19. Methods: This descriptive study was conducted to 288 patients with COVID-19 in Ahvaz (south west of Iran). Inclusion criteria were: a known case of COVID-19, willingness to participate in the study, recommendation of home quarantine from a health center, having a smartphone and fluency in reading and writing in Persian, and the exclusion criterion was a history of COVID-19 longer than three months. The data collection method was structured interviews based on a questionnaire (face to face-telephone calls-video call). Results: 45.5% of the participants in the study were women with a mean age of 37.82 (10.48) and 55.5% were men with a mean age of 36.12 (11.93%). A study of how to provide home care to patients with COVID-19 showed that in most cases, the spouse (61.4) is responsible for the care of the patient, and in other cases parents are responsible for this duty. 57.3% of the patients stated that they themselves had to leave home to provide necessities of life, and 37.2% stated that they were in charge of cooking. 47.9% of the patients evaluated the quality of self-care provided at home as good. Conclusion: During covid-19 pandemic self-care and family care to reduce the burden of the health system is very important. We must also know that this type of care requires informed and planned support along with sufficient education of the community. The health care system needs to put self-care and family among its top priorities.